2016
DOI: 10.1007/s12199-016-0537-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of health-related quality of life between type 2 diabetic patients with and without locomotive syndrome

Abstract: Objective The aim of this study was to compare healthrelated quality of life (HRQOL) between type 2 diabetic patients with and without locomotive syndrome, which is a risk for becoming bedridden because of deteriorating locomotive organs. Subjects and methods A total of 135 patients with type 2 diabetes mellitus (69.2 ± 10.2 years) were enrolled in this cross-sectional study. HRQOL was evaluated by the Euro-QOL-5 (EQ-5D), and locomotive syndrome was evaluated by ''loco-check,'' established the Japanese Orthope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
10
0
1
Order By: Relevance
“…Programs tailored specifically for individual patient needs are not well established. Recently, many studies have reported that patients with diabetes mellitus are at high risk of locomotion syndrome 7) , sarcopenia 8) and frailty 9) . Given the predicted rise in the incidence of diabetes mellitus among older patients, intervention by exercise therapy is anticipated to be used with increased regularity in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Programs tailored specifically for individual patient needs are not well established. Recently, many studies have reported that patients with diabetes mellitus are at high risk of locomotion syndrome 7) , sarcopenia 8) and frailty 9) . Given the predicted rise in the incidence of diabetes mellitus among older patients, intervention by exercise therapy is anticipated to be used with increased regularity in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients with diabetes mellitus are reported to experience impaired insulin action for various reasons, such as a decreased ability to secrete insulin, changes in body composition including increased visceral fat and decreased muscle mass, and reduced physical activity 5,6) . In these patients, the increased insulin resistance is associated with locomotive syndrome 7) , sarcopenia 8) and frailty 9) , all leading to muscle weakness 10) . These conditions predispose a patient to become bedridden.…”
Section: Introductionmentioning
confidence: 99%
“…LS refers to the conditions under which the elderly have been receiving care services, or high-risk conditions under which they may soon require care services linked to problems in their locomotive organs [30]. LS has been shown to be a risk factor for becoming bedridden by worsening motor impairment [31], and may be closely associated with decreased physical activity and motor capacity. In Japan, approximately 20% of individuals requiring 'long-term care' insurance were estimated to have an LS [31].…”
Section: Discussionmentioning
confidence: 99%
“…LS has been shown to be a risk factor for becoming bedridden by worsening motor impairment [31], and may be closely associated with decreased physical activity and motor capacity. In Japan, approximately 20% of individuals requiring 'long-term care' insurance were estimated to have an LS [31]. Therefore, LS is considered to have a high risk of causing a decrease in levels of activity in daily life and quality of life (QOL).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects answered the Loco-check questions with either "agree" or "disagree." As described in previous reports [22][23][24], if the subjects answered "agree" to one or more items on the Loco-check, they were de ned as subjects suspected to be at risk of LS (hereafter referred to as the LS-risk group). If they answered ''disagree'' to all seven items, they were de ned as no LS-risk subjects (hereafter referred to as the NLS-risk group).…”
Section: Locomotive Syndrome Risk Testmentioning
confidence: 99%